AHP & Knapsack for Better Process in Making MicroStrategy Hypercard - Khanis S Nugraha; Indriati N Bisono; Hanijanto Soewandi (Research Synergy Press, 2022)
We propose a two-stage resource allocation problem for handling RAM allocation in loading Intelligent Cubes for creating MicroStrategy Hypercard with the first stage formulated as a multi criteria problem that can be solved using Analytic Hierarchy Process (AHP) and the second stage being multiple (several) 0-1 classic Knapsack problems with constraints obtained from the first stage. When calculated in parallel, this method reduces computational complexity from O(nM) to O(1) (maxnjmaxMj). We explain our recommendation using a numerical example based on our experience.